VVV-WIT-07: another Boyajian's star or a Mamajek's object?. Issue 4 (6th November 2018) - Saito, R K; Minniti, D; Ivanov, V D; Catelan, M; Gran, F; Baptista, R; Angeloni, R; Caceres, C; Beamin, J C
ABSTRACT: We report the discovery of VVV-WIT-07, a unique and intriguing variable source presenting a sequence of recurrent dips with a likely deep eclipse in 2012 July. The object was found serendipitously in the near-IR data obtained by the VISTA Variables in the Vía Láctea (VVV) ESO public survey. Our analysis is based on VVV variability, multicolour, and proper motion (PM) data. Complementary data from the VVV eXtended survey as well as archive data and spectroscopic follow-up observations aided in the analysis and interpretation of VVV-WIT-07. A search for periodicity in the VVV K s -band light curve of VVV-WIT-07 results in two tentative periods at P  ∼ 322 d and P  ∼ 170 d. Colours and PM are consistent either with a reddened main-sequence (MS) star or a pre-MS star in the foreground disc. The near-IR spectra of VVV-WIT-07 appear featureless, having no prominent lines in emission or absorption. Features found in the light curve of VVV-WIT-07 are similar to those seen in J1407 (Mamajek's object), a pre-MS K5 dwarf with a ring system eclipsing the star or, alternatively, to KIC 8462852 (Boyajian's star), an F3 IV/V star showing irregular and aperiodic dips in its light curve. Alternative scenarios, none of which is fully consistent with the available data, are also briefly discussed, including a young stellar object, a T Tauri star surrounded by clumpy dust structure, an MS star eclipsed by a nearby extended object, a self-eclipsing R CrB variable star, and even a long-period, high-inclination X-ray binary.